Design and Fabrication of Nanostructure TiO2 Doped NiO as A Gas Sensor for NO2 Detection - Al-Taa'y, Wasan A.; Hasan, Bushra A. (Iraqi Journal of Science, 2021)
In this paper, thin films of undoped and nickel oxide (NiO) doped titanium dioxide (TiO2) were prepared using the chemical spray pyrolysis deposition (CSP) technique, with different concentrations of nickel oxide (NiO) in the range (3-9) wt%. The morphological, structural, electrical, and sensing properties of a gas of the prepared thin films were examined. XRD measurements showed that TiO2 films have a polycrystalline structure. AFM analysis showed that these films have a regular structure both before and after doping . The roughness of these films decreased after adding impurities but then the opposite of that took place. The electrical and gas sensing properties of titanium dioxide was also affected after doping. The highest sensitivity value was obtained at doping concentration of 5wt% and working temperature 473ºK.